ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT PEMANFAATAN SISTEM INFORMASI DAN PENGGUNAAN SISTEM INFORMASI PADA PASAR SWALAYAN (HYPERMARKET, SUPERMARKET DAN MINIMARKET) YANG TERDAFTAR DI JAKARTA - Rossje V. Suryaputri; Adi Widjanarko (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2012)
This study aimed to analyze the factors that affect the interest of informationsystems and use of information systems in Supermarkets are using five factors: (1) Performance Expectations, (2) Expectations Enterprises, (3) Social factors, (4) Interest Utilization and information systems (5) The conditions that facilitateusers. This study took a sample of 60 Supermarket registered in Jakarta withconvenience sampling method. Results of this study prove that performanceexpectations have an influence on the interest of information systems, whileexpectations of business and Ssocial factors has no effect on the interest ofinformation systems. While interest in the utilization of information systems andconditions that facilitate the user has an influence on the use of informationsystems.